Perancangan Sistem Informasi Persedian Barang Berbasis Web Pada Pt. Xyz (Department It Infrastructure) - Eva Sopriani; Hari Purwanto (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2023)
PT XYZ Air Jakarta is a PT which is engaged in providing clean water services for industrial areas, business areas and residential areas. The inventory information system is a system used to enter new inventory data into the database, so that there are no errors in input, output data, and report generation based on the desired data. Based on a direct survey there is division, the Itinfrastructure is still manual. So needed web inventory is to help the admin and Svp find out the information on these items and also track them. The system to be used is the programming language Java Script and MySQL. The existence of an inventory information system is expected to be useful for the Division it infrastructure, so it can be expected to reduce errors that may occur. Through this thesis, web inventory has been made in the Division IT Infrastructure.